2017
DOI: 10.1111/ahg.12210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CCAAT/Enhancer Binding Protein (C/EBP) Alpha (CEBPA) and Runt‐Related Transcription Factor 1 (RUNX1) Expression in Patients with De Novo Acute Myeloid Leukemia

Abstract: The CCAAT/enhancer binding protein (C/EBP) alpha (CEBPA) and Runt-related transcription factor 1 (RUNX1) genes have been traditionally regarded as two essential genes involved in normal myeloid maturation. Although the link between mutations in these genes and the development of acute myeloid leukemia (AML) has been extensively documented, the ramifications of gene expression dysregulations of CEBPA and RUNX1 has drawn less attention. The present study investigated CEBPA and RUNX1 gene expression levels in 96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
2
7
1
Order By: Relevance
“…Also, in the present research, a low CEBPA expression in the studied cohort was stated for the M6 case. However, a statistical significance of the difference in the CEBPA expression level between AML subtypes was confirmed probably neither in the present research nor by others [27,36], due to a small number of patients.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Also, in the present research, a low CEBPA expression in the studied cohort was stated for the M6 case. However, a statistical significance of the difference in the CEBPA expression level between AML subtypes was confirmed probably neither in the present research nor by others [27,36], due to a small number of patients.…”
Section: Discussioncontrasting
confidence: 94%
“…Thus, downregulation of CEBPA may contribute to leukemogenesis in RUNX1-mutated AML. It stays in agreement with observation of Salarpour et al which previously demonstrated that CEBPA and RUNX1 expression levels are significantly positively correlated in both AML patients and healthy volunteers, although correlation was stronger in normal control cases [27]. Researchers suggested that the regulatory network between these genes could be disrupted in AML.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As an intricate process, cell cycle regulation can undergo different alterations resulting in cell proliferation abnormalities and cancer progression. Proper cell division is ensured by various mechanisms controlling cell cycle [15,16]. These mechanisms include CDK regulation through cyclins, CDK inhibitors, and phosphorylation [17].…”
Section: (F) Expression Of P21 and P27 In T-all And B-all Patientsmentioning
confidence: 99%
“…CEBPA is a single Exon gene located on the chromosome 19 q13.1 with the length of 2783 bp. This gene belongs to the basic region leucine zipper (bZIP) family 14,15 . Its mRNA is translated to two protein isoforms using the alternative AUG initiation codons: a full-length isoform of 42 kDa and an N-terminal truncated form of 30 kDa 16 .…”
Section: Introductionmentioning
confidence: 99%